Renal abnormalities among children with sickle cell conditions in highly resource-limited setting in Ghana - Anto, Enoch Odame (PLoS One, 2019)
Sickle cell disease (SCD) is associated with progressive multi-organ failure especially, the brain and kidney and leads to high morbidity and mortality rate. The aim of this study was to determine the prevalence of renal abnormalities among children with SCD. This cross-sectional study recruited 212 sickling positive patients comprising of 96 Hb AS, 48 Hb SC, and 68 Hb SS phenotypes from the Pediatric Unit of Wassa Akropong Government Hospital, Wassa Akropong, Ghana. Early morning urine and venous blood samples were collected from each participant. Urinalysis was conducted and serum urea and creatinine levels were estimated. Estimate glomerular filtration rate (eGFR) was calculated using the Swartz equation. Classification of chronic kidney disease (CKD) was based on ‘The Kidney Disease: Improving Global Outcomes (KIDIGO)’ criteria. The mean age of the children were 7.90 years. Serum creatinine (p = 0.0310) and urea (p<0.0001) levels were significantly higher among Hb AS participants compared with Hb SS phenotype. The prevalent indicators of renal abnormalities were proteinuria (26.4%), urine granular cast (5.6%) and CKD (39.6%). Proteinuria, urine granular cast and CKD were most prevalent among Hb SS (47.1%, 11.8% and 73.5% respectively) compared with Hb SC (41.7%, 8.3%, and 45.8% respectively) and Hb AS (4.2%, 0.0%, and 14.5%) phenotypes, respectively. Sickle cell conditions were significantly associated with proteinuria (p<0.0001) and CKD (p = 0.0378). Children with Hb SS [aOR = 5.04, 95% CI (2.47–10.3); p<0.0001] and Hb SC [aOR = 3.14 95% CI (1.39–7.01); p = 0.0174] were at increased odds of developing CKD after adjusting for age, BMI and gender. Proteinuria and CKD are associated with sickle cell disease (Hb SC and Hb SS). Renal function should be routinely monitored for children with SCD.